An educational software package for CFD simulation and visualization - Manesh, Hamed Farahani; Hashemipour, Majid (My University, 2007)
The development of the Virtual Reality (VR) techniques for visualizaton of the computational simulations of complex problem has opened some new avenues for heat transfer and fluid flow research. The importance of data visualization is clearly recognized for to better understanding of the 3-D nature of the flow fields. This work introduces the educational user friendly "VRJET" package designed for teaching fluid mechanics and heat transfer. A Software is developed with C++ standard Programming language using an object-oriented approach to visualize the flow field with high performance computing including advanced support for data presentation and navigation techniques through 3D virtual environment. This work deals with 3-D visualization of the data of impinging laminar single square jet on a heated flat surface, obtained from numerical simulation. This package can be used for research, educational, and engineering. Copyright © 2007 by ASME.
2007 5th Joint ASME/JSME Fluids Engineering Summer Conference, FEDSM 2007 --
Keywords: Fluid flow research; Software package; Computational fluid dynamics; Flow visualization; Heat transfer; Virtual reality; Computer software